Exploring the Filling Related Defect in Vertical Centrifugal Castings for A413 and A356 Using 3D Transient Simulation - Mazloum, Kamar; Al Njjar, Ameen; Sata, Amit (Recent Patents on Mechanical Engineering, 2025)
BackgroundDefects in casting related to the stage of the process, like filling or solidification and related to many parameters (process, geometric, and material). In the casting field, extreme temperatures refer to the high heat necessary to melt and maintain metals or other materials in a liquid state, enabling them to be shaped into desired forms using molds. Extreme temperature and other factors, such as die rotation speed play an important role in the formation of defects, as their significant increase leads to excessive viscosity or instability in the flowing metal. The effective method that takes the least time and cost to explore this defect is simulation, and such patent-based approaches have gained attention for their potential in industrial application.ObjectiveThis study aims to predict the porosity defect for the 3D pattern in vertical centrifugal casting during filling of A413 and A356.MethodsA three-dimensional transient simulation was done for flowing mode in five molds having various aspects ratio from 1 to 2 in step 0.25 with change in pouring temperature and mold rotation speed (700 - 800°C and 50 - 150 rpm with step 25°C, 25 rpm) considering the existance of air phase with fluid inside the mold.ResultsThe study's findings reveal that when the pouring temperature exceeds 750°C and the mold rotation speed surpasses 100 RPM, porosity significantly decreases. Generally, increasing the rotation speed from 50 to 150 RPM reduces defects, except when the pouring temperature is low, specifically less than 725°C. Additionally, porosity decreases with an increase in the aspect ratio up to 2, accompanied by the lowest interface heat transfer coefficients observed at 6867.62 W/(m2·K) for A413 and 7703.89 W/(m2·K) for A356.ConclusionDetermining the interface’s heat transfer coefficient at each moment ensures accuracy and reliability in the obtained results. By following these simulations for any alloy, the quality of the castings can be improved.
Keywords: casting simulation